2004
DOI: 10.1007/s00442-004-1760-7
|View full text |Cite
|
Sign up to set email alerts
|

Do sibling tits (Parus major, P. caeruleus) disperse over similar distances and in similar directions?

Abstract: We studied dispersal movements by sibling pairs of great tits, Parus major, and blue tits, P. caeruleus, in a patchy environment, in order to test whether siblings are more similar in dispersal than expected by chance. Because of possible common environmental effects due to the heterogeneity and finiteness of the study area, we compared the similarity among siblings with the similarity between each sibling and an unrelated bird that fledged in the same patch and year, as close to the siblings' nest as possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 32 publications
2
79
0
Order By: Relevance
“…Median values of Marsh Tit NDD were substantially greater than those of breeding dispersal, as is typical of many bird species (Greenwood & Harvey 1982). NDD was similar to or shorter than comparable measures for other parids , Weise & Meyer 1979, Robbins et al 1986, van Tienderen & van Noordwijk 1988, Orell et al 1999, Matthysen et al 2005, Van de Casteele & Matthysen 2006 and Eurasian Nuthatch (Matthysen 1998). The only previous work on Marsh Tit NDD found a positive correlation with population density (Nilsson 1989), although dispersal distances were greater and population density was lower than in our study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Median values of Marsh Tit NDD were substantially greater than those of breeding dispersal, as is typical of many bird species (Greenwood & Harvey 1982). NDD was similar to or shorter than comparable measures for other parids , Weise & Meyer 1979, Robbins et al 1986, van Tienderen & van Noordwijk 1988, Orell et al 1999, Matthysen et al 2005, Van de Casteele & Matthysen 2006 and Eurasian Nuthatch (Matthysen 1998). The only previous work on Marsh Tit NDD found a positive correlation with population density (Nilsson 1989), although dispersal distances were greater and population density was lower than in our study.…”
Section: Discussionmentioning
confidence: 65%
“…The estimation of dispersal distances for this species in Sweden were hampered by low rates of subsequent detection of birds ringed as nestlings; a problem also found with Siberian Tits in Finland P. cinctus and Black-capped Chickadees P. atricapilla in British Columbia (Smith 1967, Ekman 1979, Virkkala 1990). The only relatively well-studied parids are Great Tits Parus major , which are habitat generalists with a different social behaviour to Poecile species, breeding at high densities in nestboxes and flocking in non-territorial winter groups (Dhondt & Hubl茅 1968, Dhondt 1979, Enoksson et al 1995, Verhulst et al 1997, Matthysen et al 2005. Great Tit NDDs in England exceeded that of Swedish Marsh Tits by less than half a territory width, although territories of the former were smaller and so metric distances were less (reported maxima of about 3500 m for males and about 4300 m for females) , Nilsson 1989.…”
mentioning
confidence: 99%
“…mothers and sons) breeding within the same colony due to male natal philopatry. The presence of relatives of opposite sex can also result if related offspring of both sexes disperse together to a non-natal colony, like the similarity in natal dispersal observed among sibling great tits (Matthysen et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is notable that some cases of close inbreeding resulted even though a pair of siblings had dispersed further than the median for outbreeding birds (figure 2c,g: two cases of sibling pairs inbreeding having dispersed further than the median). While it has been found that sibling tits often disperse in similar directions, but not necessarily the same distances (Matthysen et al 2005), more research is needed into the patterns of pair formation, dispersal and the break-up of family groups after fledging. We do not yet know whether brother-sister mating, the most frequent form of close inbreeding in our study population, is mainly the result of random mating between individuals that dispersed short distances or whether unusually strong pair bonds were formed while in the original family group, which may lead to restricted dispersal.…”
Section: Discussionmentioning
confidence: 99%